Prevention of needle-stick injury among nurses in an acute ward of a hospital: a best practice implementation project. Issue 2 (27th June 2022) - Huang, Hui-Mei; Chien, Hsing-Chin; Lin, Wen-ling; Chang, Chia-Hui; Chang, Mei-Yu; Su, Jui-Yuan; Mu, Pei-Fan
ABSTRACT: Objectives: This evidence implementation project aimed to identify barriers leading to needle-stick injuries (NSIs) and to develop implementation strategies to prevent NSIs in the acute ward of a hospital in central Taiwan. Introduction: The incidence rate of NSIs was 5.6% in the acute ward of a hospital in Taiwan. NSIs commonly occur during the drawing of blood, intravenous insertion, needle recapping, or performing any procedure involving sharp medical devices. NSIs are critical occupational risks among healthcare workers, possibly leading to transmission of infectious diseases, especially blood-borne viruses, such as HIV, hepatitis B, and hepatitis C. Methods: A clinical audit was undertaken using the JBI Practical Application of Clinical Evidence System (PACES) and the Getting Research into Practice (GRiP) approach. Five audit criteria that represented best practice recommendations for prevention of NSIs were used. Baseline data were collected from 177 nurses in five acute wards, followed by the implementation of multiple strategies during a 20-week period of the project. Both baseline and postimplementation audits were undertaken to determine changes in practice. Results: According to the pre-audit concerning the use of safety-engineered injection devices and safe use and disposal of needles, there was 14–15% compliance, which indicated poor compliance with current best-practice criteria. Following the project implementation, the nursing staff were educated about the well tolerated use and disposal of sharps and the improved compliance rate ranged from 40 to 96.6%, with safety needle use increasing from 16 to 95.5%, safety needle operation procedure awareness increasing from 14 to 96%, needles not recapped after use increasing from 47 to 85%, and placing used needles in the sharps collection box increasing from 75 to 80%. Conclusion: This article suggests that standardized puncture prevention education and training enhanced nurses' awareness in the acute ward.